Hopes and opportunities of stem cells from human exfoliated deciduous teeth (SHED) in cartilage tissue regeneration - Mahdavi-Jouibari, Forough; Parseh, Benyamin; Kazeminejad, Ezatolah; Khosravi, Ayyoob (Frontiers in Bioengineering and Biotechnology, 2023)
Cartilage lesions are common conditions, affecting elderly and non-athletic populations. Despite recent advances, cartilage regeneration remains a major challenge today. The absence of an inflammatory response following damage and the inability of stem cells to penetrate into the healing site due to the absence of blood and lymph vessels are assumed to hinder joint repair. Stem cell-based regeneration and tissue engineering have opened new horizons for treatment. With advances in biological sciences, especially stem cell research, the function of various growth factors in the regulation of cell proliferation and differentiation has been established. Mesenchymal stem cells (MSCs) from different tissues have been shown to proliferate into therapeutically relevant cell numbers and differentiate into mature chondrocytes. As MSCs can differentiate and integrate inside the host, they are considered suitable candidates for cartilage restructuration. These cells, which are present in the dental pulp of teeth, can proliferate when cultured under simple conditions. Dental pulp stem cells derived from exfoliated deciduous teeth (SHED) provide a novel and non-invasive source of MSCs. Due to their simple isolation, chondrogenic differentiation potential, and minimal immunogenicity, they can be an interesting option for cartilage regeneration. Recent studies have reported that SHED-derived secretome contains biomolecules and compounds that efficiently promote regeneration in damaged tissues, including cartilage. Overall, this review highlighted the advances and challenges of cartilage regeneration using stem cell-based therapies by focusing on SHED.